Overview of Viral Pneumonia Associated With Influenza Virus, Respiratory Syncytial Virus, and Coronavirus, and Therapeutics Based on Natural Products of Medicinal Plants - Hu, Ziwei; Lin, Jinhong; Chen, Jintao; Cai, Tengxi; Xia, Lixin; Liu, Ying; Song, Xun; He, Zhendan (Frontiers in Pharmacology, 2021)
Viral pneumonia has raised a serious threat to global health, especially now we have such dramatic challenges as the COVID‑19 pandemic. Approximately six million cases of CAP occur every year, and over 20% of which need for hospital admission. Influenza virus, respiratory virus, and coronavirus are three types of particularly noteworthy causative agents to investigate based on recent clinical researches. The hypersensitivity and inflammatory reactions initiated by antiviral immunity can be the major cause of the pathologic manifestations and symptoms of viral pneumonia. Therefore, we illustrated the structures and related infection mechanism of these viruses and current status of antiviral therapies in this paper. Owing to a set of antiviral regiments with unsatisfactory clinical effects result from the side effect, genetic mutation and growing incidence of resistance, more attention has been paid to the plant kingdom as a source of antiviral agents. Previous study mainly focused on plant extracts and herbal products with therapeutic efficacies against experimental models of influenza virus, respiratory virus, and coronavirus were included in the study. This review summarized the results of antiviral activity of various medicinal plants and their isolated bioactive compounds, exclusively focus on natural products for treatments on above three types of pathogens elicited pneumonia. Furthermore, we have introduced several useful screening tools to discover antiviral lead compounds.